Pengaruh Pendidikan Kewirausahaan dan Orientasi Berwirausaha Hijau terhadap Intensi Berwirausaha Hijau Mahasiswa melalui Entrepreneurial Self-Efficacy sebagai Variabel Mediasi - Khofilia Safira; Suparno Suparno; Fitra Dila Lestari (Jurnal Ilmiah Ekonomi dan Manajemen Indonesia, 2026)
This study aims to analyze the effect of entrepreneurship education and green entrepreneurial orientation on students’ green entrepreneurial intention through entrepreneurial self-efficacy as a mediating variable. The study was motivated by the relatively low level of students’ green entrepreneurial intention and the importance of promoting entrepreneurship that supports environmental sustainability. This research employed a quantitative approach using a survey method. The sample consisted of 205 students participating in the Student Entrepreneurship Program (PMW) at Universitas Negeri Jakarta selected through purposive sampling. Data were collected using questionnaires and analyzed through Partial Least Square-Structural Equation Modeling (PLS-SEM). The results indicate that entrepreneurship education and green entrepreneurial orientation have positive and significant effects on both green entrepreneurial intention and entrepreneurial self-efficacy. Entrepreneurial self-efficacy also has a positive and significant effect on green entrepreneurial intention. Furthermore, entrepreneurial self-efficacy partially mediates the effects of entrepreneurship education and green entrepreneurial orientation on students’ green entrepreneurial intention. These findings suggest that strengthening entrepreneurship education, fostering green entrepreneurial orientation, and enhancing students’ confidence in their entrepreneurial abilities can increase green entrepreneurial intention. This study contributes to the development of sustainable entrepreneurship literature and provides insights for higher education institutions in designing entrepreneurship programs that support sustainable development.